Pengaruh Celebrity Endorser Dan Word of Mouth Terhadap Keputusan Pembelian Produk Sweater Online Shop Alco Di Media Sosial Instagram - Nur Amalina Fildzah; Devilia Sari (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2017)
Alco is a small and medium businesses producing knit sweaters. Alco admitted about an increase in sales after endorsement to celebrity endorser. But there is a decline in sales in the mid 2016 even Alco been using celebrity endorser. From the initial survey results that the researcher conducted to prove recognition of Alco, these survey results showed that respondents knew Alco online shop and make a purchase decision from celebrity endorser, word of mouth, and explore Instagram. Inside Instagram, in addition to celebrity endorser that can affect a person's buying decision contained in a photo caption in the social media Instagram. And from the caption can be said as a word of mouth expressed by consumers an online shop on Instagram. explore Instagram is a feature from Instagram Thus, this study uses independent variable celebrity endorser and word of mouth. This study was conducted to know the influence of celebrity endorser and word of mouth partially and simultaneously on the purchase decision of sweater in an online shop Alco in social media Instagram. The type of research used is descriptive and causal research with the method used is quantitative. This study was involving 100 respondents of Alco consumers in social media Instagram. The sampling technique was using a non-probability sampling type of incidental sampling. This study uses multiple regression analysis technique. The results showed that simultaneously celebrity endorser and word of mouth are significantly influencing purchase decisions. Partially celebrity endorser and word of mouth are significantly influencing purchase decisions.